Weather effects on breeding parameters of two insectivorous passerines in a polluted area - Eeva Tapio; Espín Silvia; Sánchez-Virosta Pablo; Rainio Miia (ELSEVIER, 2022)
Direct and indirect effects of environmental pollution affect negatively to birds' breeding performance in both urban and industrial environments, but much less is known on how pollution and natural stress factors work together. In our long-term study (1991-2018), we explored whether industrial pollution and associated habitat changes increase the sensitivity of breeding parameters (hatching and fledging success, nestling growth) to temperature and precipitation in two insectivorous bird species, the great tit (Parus major) and the pied flycatcher (Ficedula hypoleuca). We found that both species are rather weather sensitive in terms of their fledging success, but especially in the F. hypoleuca, the negative effect was strengthened in a polluted environment. For both study species, all the breeding parameters, except growth of F. hypoleuca nestlings, were inferior in the polluted area and negatively affected by cold weather. Independent of pollution, the duration of rainy spells during the nestling period had an overall negative effect on fledging success of F. hypoleuca, and this effect became stronger at cold temperatures. The length of rainy spells was, however, positively associated with nestling wing length in both species, possibly because of better availability of some important food resources for wing growth in more humid conditions. The weather-pollution interactions in our study populations were not overwhelmingly strong, but those found in F. hypoleuca show that such interactions exist, they are species-specific and in our study system most likely associated to pollution-related resource (e.g. food) limitation. Higher sensitivity of F. hypoleuca to low temperatures is likely related to its less well-insulated nests and higher dependence on aerial prey, the availability of which is especially reduced during cold and rainy spells. Our study indicates that anthropogenic stress, such as pollution, has synergistic effects with natural stress factors affecting passerine birds' breeding performance. (C) 2020 Elsevier B.V. All rights reserved.